An improved and scalable synthesis of N-(5-(4-cyanophenyl)-3-hydroxypicolinoyl)glycine, a promising PHD2 inhibitor for the treatment of anemia. Issue 35 (26th August 2015) - Lei, Yonghua; Hu, Tianhan; Hu, Mingyang; Yang, Li; Wu, Yue; Xiang, Hua; Zhang, Lianshan; Shen, Lingjia; You, Qidong; Zhang, Xiaojin
Graphical abstract: Abstract: An improved and scalable synthetic method of N -(5-(4-cyanophenyl)-3-hydroxypicolinoyl)glycine, a promising inhibitor of PHD2, is described. The optimized route staring from commercially available 5-bromo-3-nitropicolinonitrile takes only five chemical steps and has a dramatically increased total yield of 37.6% without chromatographic purifications.